Actual Problems in the Field of Road Traffic Safety - Razzakov Mashrab Ruzievich; Ikramov Akmaljon Gofurjonovich (Genius Journals, 2022)
This article is devoted to the problems of ensuring road traffic safety, which are gaining urgent importance in our Republic today. The article mentions a number of reasons for the occurrence of road accidents and analyzes the causes of traffic accidents
Keywords: Road Infrastructure; Human Factor; Traffic Accident; Driver